2019
DOI: 10.4049/jimmunol.1900654
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Cooperates with Noncanonical NF-κB Signaling to Regulate Marginal Zone B Cell Development

Abstract: This information is current as Development Signaling to Regulate Marginal Zone B Cell B κ LSD1 Cooperates with Noncanonical NFand Jeremy M. Boss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…All chemical inhibitors were purchased from Sigma Aldrich (St. Louis, MO, USA). BMS345541, IKK16, and IMD0354 are specific inhibitors of IkB kinase (IKK) while Takinib is a specific inhibitor of TAK1 ( Figure 1 and Figure 2 ) [ 25 , 26 , 27 , 28 , 29 ]. Working stocks of 5 mg/mL were made in dimethyl sulfoxide (DMSO) for all inhibitors except for Takinib, which was dissolved at 2 mg/mL due to its lower solubility.…”
Section: Methodsmentioning
confidence: 99%
“…All chemical inhibitors were purchased from Sigma Aldrich (St. Louis, MO, USA). BMS345541, IKK16, and IMD0354 are specific inhibitors of IkB kinase (IKK) while Takinib is a specific inhibitor of TAK1 ( Figure 1 and Figure 2 ) [ 25 , 26 , 27 , 28 , 29 ]. Working stocks of 5 mg/mL were made in dimethyl sulfoxide (DMSO) for all inhibitors except for Takinib, which was dissolved at 2 mg/mL due to its lower solubility.…”
Section: Methodsmentioning
confidence: 99%
“…Conditional deletion of Lsd1 during B cell development resulted in a significant decrease in marginal zone B cells (MZB) but not on follicular B cells (FoB) 159 . MZB represent a small subset of splenic B cells that predominately respond to TI antigens 160,161 .…”
Section: Epigenetic Control Of Antibody‐secreting Cell Differentiationmentioning
confidence: 99%
“…Moreover, chromatin accessibility data indicated that NF‐κB like motifs were affected. Further analyses showed that the non‐canonical NF‐κB family member p52 interacted with LSD1, and that LSD1’s activity through the BAFF signaling pathways during transitional B cell development to MZB, was diminished in LSD1‐deficient cells 159 …”
Section: Epigenetic Control Of Antibody‐secreting Cell Differentiationmentioning
confidence: 99%
“…In plasmacytoma cell lines, LSD1 interacts with BLIMP1 to remove H3K4me1 modifications and maintain repression on B cell lineage genes including CIITA , PAX5 , and SPIB 85 . After deletion of LSD1 at the late Pro‐B cell stage in the bone marrow, LSD1 deficiency leads to a reduction in marginal zone B cells but not follicular B cells 86 . This defect in marginal zone development was mediated through an interaction of LSD1 with the non‐canonical NF‐κB transcription factor p52, encoded by NFKB2 86 .…”
Section: Epigenetic Changes Instruct B Cell Differentiationmentioning
confidence: 99%
“…After deletion of LSD1 at the late Pro‐B cell stage in the bone marrow, LSD1 deficiency leads to a reduction in marginal zone B cells but not follicular B cells 86 . This defect in marginal zone development was mediated through an interaction of LSD1 with the non‐canonical NF‐κB transcription factor p52, encoded by NFKB2 86 . In TI‐I B cell responses, LSD1 is progressively upregulated, with expression peaking in ASC and in the absence of LSD1 there is a reduction in ASC and derepression of BLIMP1 target genes 24 .…”
Section: Epigenetic Changes Instruct B Cell Differentiationmentioning
confidence: 99%